Clinical Efficacy and Safety of Shensong Yangxin Capsule-Amiodarone Combination on Heart Failure Complicated by Ventricular Arrhythmia: A Meta-Analysis of Randomized Controlled Trials - Cao, Xinfu; Zhou, Mingxue; Liu, Hongxu; Chen, Xiufen; Li, Xiang; Jia, Sihan (Frontiers in Pharmacology, 2021)
Background: Shensong Yangxin capsule (SSYX) is a well-known traditional Chinese patent medicine for treating arrhythmia. Recently, a flurry of randomized controlled trials (RCTs) of SSYX combined with amiodarone (SSYX-amiodarone) was reported in the treatment of heart failure (HF) complicated by ventricular arrhythmia (VA) in China. However, these RCTs have not been systematically evaluated. Therefore, this study aimed to evaluate the efficacy and safety of SSYX-amiodarone in the treatment of heart failure complicated by ventricular arrhythmia (HF-VA). Methods: Seven electronic literature databases (Cochrane Library, PubMed, EMBASE, China Biomedical Database web, China National Knowledge Infrastructure Databases, Chinese Scientific Journal Database and Wanfang Database) were searched from their inceptions to June 1, 2020 to identify RCTs of SSYX-amiodarone in the treatment of HF-VA. The primary outcomes included the total effective rate and adverse events (ADRs). The secondary outcomes included the frequency of ventricular premature complexes (VPCs), left ventricular ejection fraction (LVEF), N terminal pro Btype natriuretic peptide (NT-proBNP), and QT dispersion (QTd). The quality of the included RCTs was assessed using the Cochrane risk-of-bias tool. All data was analyzed using RevMan 5.3 software. The registration number of this protocol is PROSPERO CRD42020196689. Results: There are Eighteen trials involving 1,697 patients were included in this study. Meta-analysis showed that SSYX-amiodarone group was superior to amiodarone group in improving the total effective rate [RR = 1.21; 95%CI (1.16, 1.27); p < 0.01], meanwhile reducing the ADRs [RR = 0.65; 95%CI (0.45, 0.95); p = 0.03], VPCs [MD = 170.96; 95%CI (159.88, 182.04); p < 0.01] and QTd [MD = 8.39; 95%CI (6.91, 9.87); p < 0.01]. No significant difference of enhancing LVEF [MD = 4.32; 95%CI (-0.56, 9.20); p = 0.08] and reducing NT-proBNP [SMD = 0.17; 95%CI (-0.81, 1.14); p = 0.73] was observed between SSYX-amiodarone and amiodarone group. Conclusions: Despite the apparent positive findings reported, the evidence provided by this meta-analysis was still insufficient to support the routine use of SSYX-amiodarone for HF-VA due to the poor methodological quality of included studies. The overall effect should to be verified in further through more well-design clinical studies with reasonable sample and good methodological quality.